Revision of the South American genus Tetragonopterus Cuvier, 1816 (Teleostei: Characidae) with description of four new species - Silva, Gabriel S. C. [UNESP]; Melo, Bruno F. [UNESP]; Oliveira, Claudio [UNESP]; Benine, Ricardo C. [UNESP] (Magnolia Press, 2016)
The systematics of the characid genus Tetragonopterus is reviewed based on morphological and molecular data of specimens from its entire geographical range encompassing all major South American river drainages from Orinoco basin southward to the La Plata basin. Eight previously described species (T. anostomus, T. araguaiensis, T. argenteus, T. carvalhoi, T. chalceus, T. denticulatus, T. georgiae n. comb., and T. rarus) are recognized as valid, four of which are redescribed (T. argenteus, T. chalceus, T. georgiae, and T. rarus), and four new species from the Brazilian Shield in the Amazon and Sao Francisco river basins are herein described. We also provide evidence for the reallocation of Moenkhausia georgiae into Tetragonopterus and recognize T. akamai as junior synonym of T. anostomus. DNA barcodes of Tetragonopterus revealed genetic support for each recognized species and provided valuable population-level information within T. argenteus, T. chalceus, T. georgiae, and T. rarus.
Keywords: Amazon basin; Characiformes; DNA barcode; Moenkhausia; Neotropical region